Grit the Main Character in the Novel Guru Aini by Andrea Hirata: A Psychological Study of Literature - Masfufah, Elisa Raudlatul; Nuryatin, Agus; Doyin, Mukh (Universitas Negeri Semarang, 2023)
Grit is one of the characteristics needed by the current generation. In developing grit in each individual, life experiences are needed. Life experiences can be constructed through reading and appreciating literary works. One literary work (novel) that illustrates grit is the novel Guru Aini by Andrea Hirata. Through the research method of literary psychology, this study aimed to describe the dimensions of grit which include consistency of interest and persistence of effort reflected through the main character in the Guru Aini novel by Andrea Hirata. The results of this study showed that the consistency of interest reflected in the main character in the Guru Aini novel was described through five characters which include 1) consistency towards the goal; 2) the ability not to switch to another goal; 3) the ability to focus on difficult things; 4) commit to the passion; 5) the ability not to be obsessed with other things. The main character's persistence was reflected through the characters; 1) ability to not give up easily; 2) hard work; 3) responsibility; 4) diligence; 5) ability to overcome failure. The fortitude and persistence of the main character in the Guru Aini novel were expected to be a representation to convey messages through literary works so the millennial generation grows as a generation that is able to hone the human touch to prioritize the heart as a form of emotional intelligence and building grit as a form of self-consistency effort toward the goal.